OveRSoC: A Framework for the Exploration of RTOS for RSoC Platforms. (9th February 2010) - Miramond, Benoît; Huck, Emmanuel; Verdier, François; Benkhelifa, Amine; Granado, Bertrand; Lefebvre, Thomas; Aïchouch, Mehdi; Prevotet, Jean Christophe; Oliva, Yaset; Chillet, Daniel; Pillement, Sébastien
Abstract : This paper presents the OveRSoC project. The objective is to develop an exploration and validation methodology of embedded Real Time Operating Systems (RTOSs) for Reconfigurable System-on-Chip-based platforms. Here, we describe the overall methodology and the corresponding design environment. The method is based on abstract and modular SystemC models that allow to explore, simulate, and validate the distribution of OS services on this kind of platform. The experimental results show that our components accurately model the dynamic and deterministic behavior of both application and RTOS.